2020
DOI: 10.1177/0961203320969975
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pronged approach to enhance education of children and adolescents with lupus, caregivers, and healthcare providers in New Jersey: Needs assessment, evaluation, and development of educational materials

Abstract: Background: Childhood Systemic Lupus Erythematosus (cSLE) patients are younger at diagnosis and have a more severe disease course compared to adult onset SLE patients and develop significant complications related to disease and or immunosuppression. Moreover, female and minority populations experience higher rates of cSLE, with African American, Afro-Caribbean, and Hispanic populations being at greatest risk and having poor prognosis Methods: The Pediatric Alliance for Lupus initiative addressed the dearth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…On assessing mothers' total knowledge about systematic lupus erythematous, the present study showed that, less than two third of studied mothers had good level of knowledge at post and after three months of family empowerment implementation as compared to pre family empowerment implementation. That's go in the same direction with Hovde, et al (2019) (34) ,, who studied" Multi-pronged approach to enhance education of children and adolescents with lupus, caregivers, and healthcare providers in New Jersey " and found that, 86% of mothers had unsatisfactory knowledge about systematic lupus before the program implementation. While, total knowledge satisfactory level of mothers increased at immediate post and one month after the program respectively with highly statistically significant difference P <.…”
Section: Third Step: (Process Evaluation)mentioning
confidence: 74%
“…On assessing mothers' total knowledge about systematic lupus erythematous, the present study showed that, less than two third of studied mothers had good level of knowledge at post and after three months of family empowerment implementation as compared to pre family empowerment implementation. That's go in the same direction with Hovde, et al (2019) (34) ,, who studied" Multi-pronged approach to enhance education of children and adolescents with lupus, caregivers, and healthcare providers in New Jersey " and found that, 86% of mothers had unsatisfactory knowledge about systematic lupus before the program implementation. While, total knowledge satisfactory level of mothers increased at immediate post and one month after the program respectively with highly statistically significant difference P <.…”
Section: Third Step: (Process Evaluation)mentioning
confidence: 74%